(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Theoretical-practical considerations about the ritual performativity of the Amerindian shaman and the possible approximations with the expanded field of the performing arts, confronting understandings about the concepts: contemporary, modernity and archaic. Critical artistic-philosophical dialogue between the foundations of Western Kantian thought and the cannibalistic South American metaphysics. Measurements about conceptions about nature, art, aesthetics of existence, representation, theatricality, spectacle, affection, alterity, body, cosmopolitics, spirituality and dream.